Ответы и объяснения

  • mayli
  • светило науки
2012-03-21T16:37:17+00:00

1.

a) x^2+3x=0

    x(x+3)=0

    x=0, x+3=0

            x= -3

б)x-2x^3=0

   x(1-2x^2)=0

   x=0, 1-2x^2=0

           -2x^2=-1

            x^2=2

            x=+-корінь з 2

в)4-(1-х^2)=0

   4-(1-2x+x^2)=0

   4-1+2x-x^2=0

   -x^2+2x+3=0

   D=16

   x1=-1, x2=3

г)x^2/8=x/2 (обидві частини цього рівняння домножимо на 8)

  x^2=4x

  x^2-4x=0

  x(x-4)=0

  x=0, x-4=0

         x=4

2. (8x-x^2)/3=(x^2-2x)/2 (обидві частини цього рівняння домножимо на 6)

    2(8x-x^2)=3(x^2-2x) 

    16x-2x^2=3x^2+6x

    16x-2x^2-3x^2+6x=0

    -5x^2+22x=0

    -x(5x-22)=0

     x=0, 5x-22=0

             5x=22

             x=4,4